The Study of Nebular Emission on Nearby Spiral Galaxies in the IFU Era - Fernando Fabián Rosales-Ortega (Advances in Astronomy)
A new generation of wide-field emission-line surveys based on integral field units (IFU) is allowing us to obtain spatially resolved information of the gas-phase emission in nearby late-type galaxies, based on large samples of HII regions and full two-dimensional coverage. These observations are allowing us to discover and characterise abundance differentials between galactic substructures and new scaling relations with global physical properties. Here I review some highlights of our current studies employing this technique: (1) the case study of NGC 628, the largest galaxy ever sampled with an IFU; (2) a statistical approach to the abundance gradients of spiral galaxies, which indicates a universal radial gradient for oxygen abundance; and (3) the discovery of a new scaling relation of HII regions in spiral galaxies, the local mass-metallicity relation of star-forming galaxies. The observational properties and constrains found in local galaxies using this new technique will allow us to interpret the gas-phase abundance of analogue high-z systems.